Challenges of Implementing the “Additional Protocol to the European Charter of Local Self-Government on the Right to Participate in the Affairs of a Local Authority” in Georgia - Kakhidze, Irakli (Journal of Law, 2022)
Democracy implies not only the existence of elected representatives, but also the existence of active and politically engaged citizens. People's participation in the exercise of government is the basic essence, ground and purpose of democracy. The present article analyzes the environment and practice of citizens' participation in the implementation of local self-government in Georgia. The article talks about the challenges in Georgia in the mentioned field, their causes and ways to solve them.